ОБМЕЖУВАЛЬНІ ЗАХОДИ КРИМІНАЛЬНО-ПРАВОВОГО ХАРАКТЕРУ: ОКРЕМІ МІРКУВАННЯ З ПРИВОДУ НОРМАТВИНОЇ ВИЗНАЧЕНОСТІ ПРИЧИННО- ФАКТОРНОГО КОМПЛЕКСУ ЇХ ЗДІЙСНЕННЯ ТА ЗАГАЛЬНИХ ЗАСАД ЗАСТОСУВАННЯ (Вісник Кримінологічної асоціації України, 2022)
The article is devoted to the study of the causal complex of restrictive measures of criminal law and general principles of their application and development on this basis of their own generalized conclusions aimed at further development of scientific understanding of the prerequisites and grounds for their implementation and improvement of law enforcement practice through compliance with certain rules or criteria.
Keywords: restrictive measures, domestic violence, abuser, victim of domestic violence, interests of the victim.